2010
DOI: 10.1681/asn.2010040377
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic Inhibition of ENaC Produces Aldosterone Escape

Abstract: The mechanisms underlying "aldosterone escape," which refers to the excretion of sodium (Na ϩ ) during high Na ϩ intake despite inappropriately increased levels of mineralocorticoids, are incompletely understood. Because local purinergic tone in the aldosterone-sensitive distal nephron downregulates epithelial Na ϩ channel (ENaC) activity, we tested whether this mechanism mediates aldosterone escape. Here, urinary ATP concentration increased with dietary Na ϩ intake in mice. Physiologic concentrations of ATP d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
110
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(118 citation statements)
references
References 46 publications
8
110
0
Order By: Relevance
“…'Aldosterone escape' refers to the excretion of sodium during high sodium intake; local purinergic tone in the aldosterone-sensitive distal nephron downregulates ENaC activity. P2Y 2 −/− mice had significantly less increased sodium excretion than wild-type mice [354]. It was concluded that control of ENaC by purinergic signalling is necessary for aldosterone escape and this was supported by another laboratory in a later paper, and in addition, it identified a potential role for NO and prostaglandins in response to aldosterone [434].…”
Section: Distal Tubulesmentioning
confidence: 87%
“…'Aldosterone escape' refers to the excretion of sodium during high sodium intake; local purinergic tone in the aldosterone-sensitive distal nephron downregulates ENaC activity. P2Y 2 −/− mice had significantly less increased sodium excretion than wild-type mice [354]. It was concluded that control of ENaC by purinergic signalling is necessary for aldosterone escape and this was supported by another laboratory in a later paper, and in addition, it identified a potential role for NO and prostaglandins in response to aldosterone [434].…”
Section: Distal Tubulesmentioning
confidence: 87%
“…ENaC could also be considered a candidate mediator of escape (26). Although protein levels have been shown to be inconsistently regulated in this model across studies, it is possible that the activity of the whole channel is regulated in another fashion, perhaps by proteolytic cleavage or trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, our data support the concept that extracellular nucleotides facilitate natriuresis; they also reveal an aldosterone-independent downregulation of major renal sodium transporters and channel subunits by purinergic signaling. purinergic receptors; extracellular nucleotides; ectonucleotidases; nucleoside triphosphate diphosphohydrolase-1; aldosterone; sodium transporters EXTRACELLULAR NUCLEOTIDES (ATP/ADP/UTP), acting through type-2 purinergic receptors (P2), potentially regulate renal tubular transport of water and sodium, and thereby urinary concentrating ability (5,7,11,18,19,23,25,26,28,29,33,39). P2 receptor signal modulation is controlled by a narrow range of extracellular concentrations of ATP and related nucleotides, which are mediated through regulated release from cells and rapidly hydrolyzed by ectonucleotidases (10).…”
mentioning
confidence: 99%
“…The recent discoveries that Panx1 channels serve as K ϩ sensors for changes in the extracellular milieu (29,34,39) may help establish further links between renal tubular K ϩ , ATP, and purinergic signaling (11). Therefore, via ATP release and purinergic inhibition of renal epithelial salt and water transport, Panx1 may participate in important renal physiological mechanisms such as high-K ϩ diet-induced elevations in tubular flow, the aldosterone paradox, and aldosterone escape (11,38).…”
Section: Discussionmentioning
confidence: 99%